Dinamika Penggunaan Bahasa Indonesia Di Era Milenial - Laudya Chintya H; M Anggara Mulia; Margaretha Situmorang; M. Surip (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
In the progress of the times, the use of the Indonesian language has gradually changed, there are several words in the Indonesian language whose reading has been changed, which has had a significant impact on the position of the Indonesian language as a national language and the nation's cultural identity. In this millennial era, many generations have grown up in an environment filled with technology which has made big changes in terms of communicating formally and informally. The influence of globalization and the popularity of English has also caused a shift communication preferences, where Indonesian may be less attractive to the Millennial Generation. Through literature review, data search was carried out to identify the language styles of the millennial generation and analyze it to find out the impact of using this language style. Search results shows the impact of the millennial generation's language style on the integrity of the Indonesian language in this era of globalization.